Residual wood polymers facilitate compounding of microfibrillated cellulose with poly(lactic acid) for 3D printer filaments. (25th December 2017) - Winter, Armin; Mundigler, Norbert; Holzweber, Julian; Veigel, Stefan; Müller, Ulrich; Kovalcik, Adriana; Gindl-Altmutter, Wolfgang
Abstract : Microfibrillated cellulose (MFC) is a fascinating material with an obvious potential for composite reinforcement due to its excellent mechanics together with high specific surface area. However, in order to use this potential, commercially viable solutions to important technological challenges have to be found. Notably, the distinct hydrophilicity of MFC prevents efficient drying without loss in specific surface area, necessitating storage and processing in wet condition. This greatly hinders compounding with important technical polymers immiscible with water. Differently from cellulose, the chemistry of the major wood polymers lignin and hemicellulose is much more diverse in terms of functional groups. Specifically, the aromatic moieties present in lignin and acetyl groups in hemicellulose provide distinctly less polar surface-chemical functionality compared to hydroxyl groups which dominate the surface-chemical character of cellulose. It is shown that considerable advantages in the production of MFC-filled poly(lactic acid) filaments for three-dimensional printing can be obtained through the use of MFC containing residual lignin and hemicellulose due to their advantageous surface-chemical characteristics. Specifically, considerably reduced agglomerations of MFC in the filaments in combination with improved printability and improved toughness of printed objects are achieved. This article is part of a discussion meeting issue 'New horizons for cellulose nanotechnology'.